ChemInform Abstract: Structure and Magnetic Behavior of Layered Honeycomb Tellurates, BiM(III)TeO6 (M: Cr, Mn, Fe). Issue 51 (5th December 2016) - Kim, Sun Woo; Deng, Zheng; Fischer, Zachary; Lapidus, Saul H.; Stephens, Peter W.; Li, Man‐Rong; Greenblatt, Martha
Abstract: The title tellurates are prepared as polycrystalline samples by calcination of stoichiometric amounts of Bi2 O3, M2 O3, and TeO3 in air (Al2 O3 crucible, 750 °C, 24 h).